2016
DOI: 10.1007/s12325-016-0407-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Daclatasvir Drug–Drug Interactions

Abstract: The treatment of hepatitis C virus (HCV) infection has been revolutionized in recent years by the development of direct-acting antiviral regimens that do not contain peginterferon (pegIFN) and/or ribavirin (RBV). While direct-acting antiviral-based regimens have been shown to be greatly superior to pegIFN/RBV-based regimens in terms of efficacy and safety, they have a greater susceptibility to drug–drug interactions (DDIs). Daclatasvir (DCV)—the benchmark pangenotypic nonstructural protein 5A inhibitor—has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
2
16
0
3
Order By: Relevance
“…The primary route of elimination for daclatasvir is the feces (88%), predominantly as the parent, with little renal excretion (6.6%). Daclatasvir is a substrate for CYP3A and P-gp and is an inhibitor of P-gp/BCRP and OAT1B1/3 (Garimella et al, 2016;Daklinza, 2017).…”
Section: Daclatasvirmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary route of elimination for daclatasvir is the feces (88%), predominantly as the parent, with little renal excretion (6.6%). Daclatasvir is a substrate for CYP3A and P-gp and is an inhibitor of P-gp/BCRP and OAT1B1/3 (Garimella et al, 2016;Daklinza, 2017).…”
Section: Daclatasvirmentioning
confidence: 99%
“…Sofosbuvir, ledipasvir, velpatasvir, and elbasvir are not expected to perpetrate any metabolic enzyme-mediated DDIs. Although daclatasvir may induce CYP3A, several clinical studies with coadministered CYP3A substrates have demonstrated that daclatasvir is unlikely to elicit clinically relevant interactions (Garimella et al, 2016).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Among Direct Acting Antiviral (DAA)-based treatment regimens for chronic HCV infection, the combination of daclatasvir and sofosbuvir has shown manageable interactions with anti-HIV drugs (7). Given the fact that daclatasvir is a substrate of CYP3A4 and that regimens containing etravirine and efavirenz decrease daclatasvir exposure through CYP3A4 induction, it seems necessary to increase the dose of daclatasvir to 90 mg daily in order to minimize the drug interactions (2,3,8).…”
mentioning
confidence: 99%
“…Moreover, concomitant prescription of daclatasvir with antiretroviral regimens, which contain atazanavir/ritonavir and inhibit CYP3A4, would cause a 2.1-fold increase in the area under the curve (AUC) of daclatasvir (8). Likewise, a combination of atazanavir and cobicistat exhibits the same interactions with daclatasvir.…”
mentioning
confidence: 99%
See 1 more Smart Citation